Education of Students with Disabilities, Science, and Randomized Controlled Trials. (September 2021) - Odom, Samuel L.
The purpose of this article is to examine the application of randomized controlled trial (RCT) methodology for determining the efficacy of school-based interventions in general and special education. In education science, RCTs are widely acknowledged as the gold standard of efficacy research, with other methodologies relegated to a lower level of credibility. However, scholars from different disciplines have raised a variety of issues with RCT methodology, such as the utility of random assignment, external validity, and the challenges of applying the methodology for assessing complex service interventions, which are necessary for many students with disabilities. Also, scholars have noted that school-based RCT studies have largely generated low effect sizes, which indicate that the outcomes of the interventions do not differ substantially from services as usual. The criticisms of RCT studies as the primary methodology in school-based intervention research for students with disabilities are offered along with recommendations for extending the acceptability of a broader variety of research approaches.